Voluntary activity in Marco Aurelio - Gagin, François (Estudios de Filosofía, 2002)
The first focus of the article consists of an analysis and a questioning on the use of the term will in Stoicism and its translation in Greek. This analysis reveals that the expression voluntary activity fully translates the specificity of this world system which is the philosophy of the portico. Then, the very exercise of philosophy, which is an implementation of physical, logical and ethical knowledge, is observed through each of the emperor’s meditations as an effort to cultivate the main part of the soul. Thus, the inner perfection achieved includes a feeling of human brotherhood and cosmic solidarity linked to one of the essential dogmas of the school: living in accordance with nature.